Using costing techniques based on time-oriented functions and target costing to improve product value: an applied study in the General Company for Textile Industries in Hilla - Najaf Men’s Clothing Factory - Shaker Abdul Karim Al Baldawi; Salah Mahdi Al-Kawaz (Iraqi Journal for Administrative Sciences, 2024)
The concept of the product value and how to improve it is becoming increasingly used in recent years as a result of the rapid developments taking place in the modern business environment , such as increased competition , the technological progress, the short product life cycle , globalization of markets, and therefore this has led to a diversity of customers' requirements and needs into a product leadsto the achievement of value added to him through harmony of the functional characteristics for the product with these requirements and have low prices and quality matched saturated and expectations as a basic hub on which to compete by economic units . So can say that economic units if it wants to keep pace with these developments, it should search for techniques that help them to improve of theirproducts value through cost reducing and maintain on the quality, including Time-Driven Functions- based Cost and target costing as important techniques in the product design stage . Therefore , the problem that can be framed in this research centered on the following basic question: Is that the using of the Time-Driven Functions- based Costand target costing techniquesleads to improve of products value through cost reducing and maintain on the quality? . Finally, a number of recommendations has been put on the light of conclusions reached .